Endoscopic CO(2) Laser Horizontal Partial Laryngectomy in Larynx Carcinosarcoma. (14th July 2014) - Ciorba, Andrea; Bianchini, Chiara; Iannini, Valeria; Faita, Antonio; Bianchini, Enzo; Stomeo, Francesco; Pelucchi, Stefano; Pastore, Antonio
Abstract : Background. Carcinosarcoma is an extremely rare malignant neoplasm, with both a malignant epithelial and mesenchymal component, that rarely affects the larynx. Aim. Aim of this paper is to describe the case of a patient affected by a larynx carcinosarcoma treated by endoscopic horizontal partial laryngectomy with CO(2) laser and particularly discuss the histogenetic hypothesis as well as the possible treatment modalities of this rare lesion. Methods. Case report and literature review. Discussion and Conclusion. Still little is known about the biology of carcinosarcoma and there is still no consensus in the literature on the treatment of these tumors. Endoscopic horizontal partial laryngectomy could represent another treatment option in selected cases.